The Effect of Profitability, Liquidity, Solvency and Firm Size on Debt Policy in Healthcare Companies (2019-2023) - Elsa Rahmawati; Latifah Selamita; Benny Dheyanto; Krisdiana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to examine how profitability, liquidity, solvency, and firm size influence debt policy in healthcare companies listed on Indonesia Stock Exchange (IDX). Annual financial reports that are accessible on each company’s website and official IDX website (www.idx.co.id) provide secondary data for this study. From 2019 to 2023, 34 healthcare companies listed on IDX make up population. A total of 43 observations were obtained after the outlier removal process by selecting 9 companies that satisfied criteria using a purposive sampling method. Data was analyzed using multiple linear regression. The findings indicate that profitability does not significantly impact debt policy. On other hand, liquidity and firm size have a significant negative impact, while solvency significant positive impact on debt policy.